Adsorption of antitumor antibiotic doxorubicin on MCM-41-type silica surface - Nadiia V Roik; Lyudmila A Belyakova; Marina O Dziazko (Adsorption Science & Technology)
The aim of this study was to evaluate the adsorption behavior of doxorubicin on MCM-41 silica, which was synthesized by templated sol–gel method, as a function of contact time, pH of solution, and drug equilibrium concentration. Experimental kinetic curves of adsorption were compared with theoretical models of Lagergren and Ho-McKay for pseudo-first- and pseudo-second-order processes. Equilibrium adsorption of doxorubicin was analyzed by Langmuir, Freundlich, Redlich–Peterson, and Brunauer–Emmet–Teller isotherm models. These results can be the basis for direct modification of MCM-41-type silicas sorption activity to drugs.